Tricarboxylic acid cycle intermediate pool size: Functional importance for oxidative metabolism in exercising human skeletal muscle - Bowtell, J. L.; Marwood, S.; Bruce, M.; Constantin-Teodosiu, D.; Greenhaff, P. L. (Sports Medicine, 2007)
The tricarboxylic acid (TCA) cycle is the major final common pathway for oxidation of carbohydrates, lipids and some amino acids, which produces reducing equivalents in the form of nicotinamide adenine dinucleotide and flavin adenine dinucleotide that result in production of large amounts of adenosine triphosphate (ATP) via oxidative phosphorylation. Although regulated primarily by the products of ATP hydrolysis, in particular adenosine diphosphate, the rate of delivery of reducing equivalents to the electron transport chain is also a potential regulatory step of oxidative phosphorylation. The TCA cycle is responsible for the generation of [almost equal or equal to]67% of all reducing equivalents per molecule of glucose, hence factors that influence TCA cycle flux will be of critical importance for oxidative phosphorylation. TCA cycle flux is dependent upon the supply of acetyl units, activation of the three non-equilibrium reactions within the TCA cycle, and it has been suggested that an increase in the total concentration of the TCA cycle intermediates (TCAi) is also necessary to augment and maintain TCA cycle flux during exercise.